PHARMACOTHERAPY FOR HIGH BLOOD PRESSURE AT THE CONSULTATION SERVICE OF ABIDJAN HEART INSTITUTE (CÔTE D'IVOIRE) - Etienne Effo; Eric Tia; Ephraïm Alliman; Geneviève Irié-N'Guessan; Gisèle Kouakou-Siransy (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
High blood pressure is a cardiovascular disease that, if not well treated, can lead to complications. In fact, only 55% of people suffering from high blood pressure treated, have a controlled blood pressure. A rigorous pharmacotherapy approach based on the rational use of antihypertensive drugs could help to improve this figure. This study aimed to investigate the pharmacotherapy for high blood pressure at the consultation department of the Abidjan Heart Institute. This descriptive retrospective study focused on patient records received from 2019 to 2021. It consisted of collecting data on patients receiving consultations, for prescription of antihypertensive drugs and their follow-up. Therefore, compliance of requirements with national and international recommendations were sought. The study population of 251 patients was female dominated (sex ratio: 1.3) with a mean age of 55.94±12.51 years. Risk factors included aging (40.64%), menopause (72.54%), female (56.57%) and BMI (31.47%).  All stages of high blood pressure were represented, including controlled hypertension (27.09%) and type 1 hypertension (26.69%). Management protocols were based on ESC/ESH recommendations. Prescriptions for monotherapy, bitherapy, tritherapy, quadritherapy and pentatherapy showed a satisfactory level of compliance. Patient follow-up showed a significant increase (54.9%) in controlled hypertension and a non-significant reduction (20.1%) in type 2 hypertension. The pharmacotherapy for high blood pressure at the consultation service of Abidjan Heart Institute showed a satisfactory level of compliance in the approach.